PENERAPAN DISIPLIN PROTOKOL KESEHATAN DI ERA NEW NORMAL PANDEMI COVID-19 PADA ANAK USIA DINI DI RA MUSLIMAT NU 15 MALANG - Erza Ayu Sulistyorini; Anwar Sa’dullah; Mutiara Sari Dewi (Jurnal Dewantara, 2021)
Health protocols is very important to be applied by all parties, because considering this virus can quickly spread, spread and infect anyone regardless of age, including early childhood. Children are vulnerable to the risk of transmission of Covid-19. Therefore, the application of health protocols needs to be taught, implemented and trained from an early age so that children can adapt to new normal situations and carry out activities safely and protected from Covid-19 transmission. The purpose of this study was to describe the condition of student discipline at RA Muslimat NU 15 Malang towards the health protocol, and the efforts made by the school, as well as the obstacles during its application to students. The method used in this research is a qualitative case study. Data was collected by means of observation, interviews and documentation. Based on the results of the study, it shows that student discipline towards health protocols can be said to be good, besides that the facilities and facilities provided by the school have been fulfilled to support the application of health protocol discipline, and obstacles to students come from various factors, namely the environment, from within the students themselves. and a lack of regulatory emphasis from schools.